Peculiarities of the online teaching process organisation as a form of physical training lessons - Mykola Shapovalov; Ruslana Sushko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to investigate modern approaches to the online teaching process during physical training lessons at schools. Material and methods: analysis of scientific and methodological literature along with Internet informative data; questionnaire using google-forms; methods of mathematical statistics were applied, a survey of 95 secondary schools pupils in Kyiv and Bila Tserkva cities was organised. Results: current state of this issue regarding the online teaching process organisation was analysed. It has been determined that the physical training lessons organisation has predominantly a formal nature, it is ineffective and must undergo fundamental changes; it cannot be an alternative to practical training in the gym, only as its addition. Assessment of pupils' satisfaction with physical training lessons provided justification for understanding the problems of online lessons organisation, the necessity for changes in approaches to teaching of physical education specialists, what exactly it would make sense to add to the physical training lessons organisation during online lessons in order to meet effectively the requirements of a modern student needs. Conclusions: it was revealed that the level of satisfaction with physical training lessons among students in conditions of lockdown restrictions depends directly on the interest, responsibility, professionalism of the mentor and active student-teacher feedback. The absence of the components mentioned before neutralises the harmonious development of a pupil and provokes negative consequences. The predominant pupils' interest to obtain knowledge, skills and abilities provided by physical training teachers was specified.